Respuesta :

Answer:

Point Form:

( − 2 , 3 )

Equation Form:

x  =  − 2 ,  y  =  3

Step-by-step explanation:

Add the equations in order to solve for the first variable. Plug this value into the other equations in order to solve for the remaining variables.

Answer:

x = -2, y = 3

Step-by-step explanation:

x + 3y = 7

2x + 4y = 8

Make the x term the same for both equations by multiplying the first equation by 2.

Now you have two equations with the same x terms.

2x + 6y = 14

2x + 4y = 8

Take the larger equation from the smaller to remove the x terms from the equations.

2x + 6y = 14

                   -

2x + 4y = 8

2y = 6

y = 3

Put the known y term back into the equations to find the y term

3(3) + x = 7

9 + x = 7, x = -2

12 + 2x = 8

2x = -4, x = -2

ACCESS MORE